Significant production of vanillin and in vitro amplification of ech gene in local bacterial isolates - Mazhar,B. (2023)
Abstract Vanillin is the major component which is responsible for flavor and aroma of vanilla extract and is produced by 3 ways: natural extraction from vanilla plant, chemical synthesis and from microbial transformation. Current research was aimed to study bacterial production of vanillin from native natural sources including sewage and soil from industrial areas. The main objective was vanillin bio-production by isolating bacteria from these native sources. Also to adapt methodologies to improve vanillin production by optimized fermentation media and growth conditions. 47 soil and 13 sewage samples were collected from different industrial regions of Lahore, Gujranwala, Faisalabad and Kasur. 67.7% bacterial isolates produced vanillin and 32.3% were non-producers. From these 279 producers, 4 bacterial isolates selected as significant producers were; A3, A4, A7 and A10. These isolates were identified by ribotyping as A3 Pseudomonas fluorescence (KF408302), A4 Enterococcus faecium (KT356807), A7 Alcaligenes faecalis (MW422815) and A10 Bacillus subtilis (KT962919). Vanillin producers were further tested for improved production of vanillin and were grown in different fermentation media under optimized growth conditions for enhanced production of vanillin. The fermentation media (FM) were; clove oil based, rice bran waste (residues oil) based, wheat bran based and modified isoeugenol based. In FM5, FM21, FM22, FM23, FM24, FM30, FM31, FM32, FM34, FM35, FM36, and FM37, the selected 4 bacterial strains produced significant amounts of vanillin. A10 B. subtilis produced maximum amount of vanillin. This strain produced 17.3 g/L vanillin in FM36. Cost of this fermentation medium 36 was 131.5 rupees/L. This fermentation medium was modified isoeugenol based medium with 1% of isoeugenol and 2.5 g/L soybean meal. ech gene was amplified in A3 P. fluorescence using ech specific primers. As vanillin use as flavor has increased tremendously, the bioproduction of vanillin must be focused.